CEO attributes, board independence on earnings management: Evidence from companies listed on the Indonesia Stock Exchange - Ika Pratiwi; Aryo Bimo Setya Permana; Rissa Anandita; Raden Roro Diana Atika Ghozali; Siti Noor Aini Hidayah (Proceeding International Conference on Accounting and Finance, 2026)
The purpose of this study is to examines the effect of CEO attributes and board independence on earnings management of listed firms in Indonesia Stock Exchange in year 2021-2024. The data comprises firms composed from 2021 to 2024 for the non-financial sector companies listed on the BEI. There are 110 companies and 440 data that fall into the criteria based on the purposive sampling method. Multiple Regression Analysis as data analysis techniques used SPSS software (version 21.0). CEO attributes, which are proxied by CEO financial expertise, CEO compensation, CEO nationality, female CEO and board independence as independent variables is measured by collected data from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2024. Earnings management is dependent variable is measured by Discretionary accruals are calculated by subtracting total accruals from nondiscretionary accruals. The empirical results shows that CEO attributes and board independent have significant effect on earnings management. Many studies focus on only one CEO attribute or one aspect of board governance. Rarely does research combine CEO attributes and board independence simultaneously to examine their combined effects on earning management. The novelty of this research is combining CEO attributes and board independence. This research examines both factors simultaneously or testing the combined effect of executive leadership and board quality on earnings management. Providing a more comprehensive understanding of how managerial and board structures jointly influence earnings management practices. The study offers an important reference for academics and industry professionals seeking to explore the determinants of earnings management practices in the manufacturing industry.